2016
DOI: 10.1055/s-0042-111389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of the Omni mode for detecting video capsule endoscopy images: A multicenter randomized controlled trial

Abstract: Background and study aims: Olympus recently developed a new algorithm called Omni mode that discards redundant video capsule endoscopy (VCE) images. The current study aimed to demonstrate the non-inferiority of the Omni mode in terms of true positives (TPs) and the superiority of the Omni mode with regard to reading time against a control (ordinary ES-10 system). Patients and methods: This multicenter prospective study included 40 patients with various small bowel diseases. VCE images were evaluated by 7 reade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…We conducted a multicenter study in Japan and reported the efficacy of omni mode. 36 We did not demonstrate non-inferiority between using control (normal reading) and omni mode. However, detection of major lesions was not significantly different between control and omni modes.…”
Section: Current Status Of Reading Software For Sbcementioning
confidence: 52%
See 3 more Smart Citations
“…We conducted a multicenter study in Japan and reported the efficacy of omni mode. 36 We did not demonstrate non-inferiority between using control (normal reading) and omni mode. However, detection of major lesions was not significantly different between control and omni modes.…”
Section: Current Status Of Reading Software For Sbcementioning
confidence: 52%
“…Omni mode can select and discard redundant images, and display all the areas captured by SBCE. We conducted a multicenter study in Japan and reported the efficacy of omni mode . We did not demonstrate non‐inferiority between using control (normal reading) and omni mode.…”
Section: Current Status Of Reading Software For Sbcementioning
confidence: 82%
See 2 more Smart Citations
“…This software has been recently superseded by the Omni mode, which claims to be able to reduce the images displayed by 65% through the ‘intelligent’ removal of repeated as well as overlapping images. To date this has been studied in a Japanese multicentre trial, which showed that this software was able to correctly remove images while maintaining all the preidentified major lesions in 40 selected cases 52. A larger multicentre European study is currently underway.…”
Section: Introductionmentioning
confidence: 99%